Penerapan Metode Multi Atribut Utility Theory Dalam Sistem Seleksi Penerimaan Dosen Di Stmik-Amik-Riau. - Hadi Asnal; Fransiskus Zoromi (LPPM Universitas Abdurrab, 2020)
STMIK Amik Amik Riau is an institution of higher education that focuses on computer science, in the learning process required by lecturers with the best qualifications, to get lecturers with the best qualifications needed for an objective selection process, and a system that can be built to be used to involve this selection process, a system built using the multi-attribute utility theory method, the multi-attribute utility theory method will be used to process predetermined criteria, and this criterion will be processed into a recommendation. Multi attribute attribute theory is used to compare quantitative values ​​that combine measurements from existing values. Multi-attribute utility theory is also used to convert several criteria into numerical values. The author agrees that this system provides solutions to existing problems and provides recommendations to leaders in determining decisions.